Barriers to electric vehicle uptake in Ireland: Perspectives of car-dealers and policy-makers. Issue 1 (March 2019) - O'Neill, Eoin; Moore, Dave; Kelleher, Luke; Brereton, Finbarr
Highlights: Uptake of EVs in Ireland lags EU peers with only 4000 EVs on Irish roads in 2017. Incentives structures deliver poor CO2 reductions in proportion to policy costs. Absence of clear signals over the future of diesel vehicles undermines EV uptake. A responsive policy approach can advance EV uptake and transition away from diesel. Abstract: This study explores barriers to the uptake of plug-in electric vehicles (EVs) using the case of Ireland, a country which lags well behind the adoption rates of neighbouring countries with EVs representing a market share of just 0.7% of new vehicles in 2017. The article investigates the mismatch between early aspirations, policy and infrastructure interventions and the outcomes achieved, presenting findings from semi-structured interviews with policy-makers and car dealership representatives. These point to progress being limited by a lack of sustained promotion and awareness-raising around EVs, an over-reliance on fiscal instruments and weaknesses in an incentive regime that has remained static throughout, despite limited results and progressively poorer CO2 reductions in proportion to policy costs. The study also identifies a steep rise in used diesel vehicle imports from the UK market following the Brexit vote as potentially further impairing Ireland's progress on transport decarbonisation. Moreover, it is suggested that EV policy has been weakened by the avoidance of clear signals over the future of diesel vehicles, even as this has been called into question internationally. The case is seen to present important lessons on the need to maintain responsive national EV policies as the development of plug-in technologies progresses.